No decline in investment in public-sector energy and water supply - Astrid Cullmann; Maria Nieswand; Caroline Stiel (DIW Economic Bulletin, 2015)
A considerable share of public investment comes not only from public budgets but also from public utility companies. One major area of investment is energy and water supply, where the utility companies have substantial fixed assets in the form of distribution infrastructure. Using new microdata which has not been analyzed before, the present report shows that-unlike with the core public budgets-public energy and water supply companies show no signs of insufficient investment. On the contrary, gross investment into distribution networks over the past ten years has shown an upward trend comparable to that of private energy and water supply companies-if investment related to the expansion of infrastructure resulting from the energy transition is not taken into account. In addition, no clear correlation was found between the investment expenditure of energy and water supply companies and the financial strength or demographic trends within a given region. However, this does not rule out the possibility of diverging investment trends in the near future in response to demographic changes.
Keywords: R53; L33; L97; 330; Investments; Public Utilities